Pengembangan Onlineshop di Kalangan Masyarakat Menengah Kebawah Di Baloi Indah, Kecamatan Lubuk Baja, Kelurahan Baloi Indah, Batam - Vicky Darwinto; Rino Rino; Nelson Tan; Hakim Agung; Qaadir Qaadir; Wini Alvita; Rizky Fernando; Milenia Ong; Jose Armando (National Conference for Community Service Project (NaCosPro), 2019)
A program aimed in order to improve and increase their economy by using a Dropship/Online shop and to additional income for the housewife to help their husband to raise their family and so in the future they can offer job vacancy.